2022
DOI: 10.3389/fped.2022.805440
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Primary School Teachers and Its Associated Factors Toward Students With Attention Deficit Hyperactivity Disorder in Debre Markos and Dejen Towns, Northwest Ethiopia

Abstract: BackgroundAlthough most instructors appear to understand visible disability, they appear to have a negative attitude toward children with attention deficit hyperactivity disorder (ADHD), considering them to be lazy or purposefully disruptive. In Ethiopia, there is a scarcity of data on teachers’ attitudes toward children with ADHD.MethodsAn institution-based cross-sectional study was conducted. A pre-tested questionnaire that contains a case vignette was administered through face-to-face interview with 417 tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…These findings mirror previous research which reported that post-primary teachers viewed the behaviour of students with ADHD as disruptive (Krtek et al, 2022) and similar attitudes have also been reported among primary school teachers in Ireland (Ward, 2014) and internationally (Amha & Azale, 2022;Mahdi & Al-Juboori, 2021;Schatz et al, 2021). Perceptions that students with ADHD negatively impact teaching and learning, reduce the amount of time available for others, and thereby compromising everyone's ability to learn are also supported by earlier research among Canadian elementary teachers (Blotnicky-Gallant et al, 2015).…”
Section: Students With Adhd and The Impact On Teaching And Learningsupporting
confidence: 89%
“…These findings mirror previous research which reported that post-primary teachers viewed the behaviour of students with ADHD as disruptive (Krtek et al, 2022) and similar attitudes have also been reported among primary school teachers in Ireland (Ward, 2014) and internationally (Amha & Azale, 2022;Mahdi & Al-Juboori, 2021;Schatz et al, 2021). Perceptions that students with ADHD negatively impact teaching and learning, reduce the amount of time available for others, and thereby compromising everyone's ability to learn are also supported by earlier research among Canadian elementary teachers (Blotnicky-Gallant et al, 2015).…”
Section: Students With Adhd and The Impact On Teaching And Learningsupporting
confidence: 89%
“…However, the percentage of participants who had undergone such training was comparatively lower than a previous study conducted in Isfahan, where half of the participants had received training courses specifically focused on ADHD [7]. However, this finding was higher than studies conducted in Amhara where most participants did not have any workshops, training, or courses regarding ADHD [10]. This is similar to a study done in Ethiopia where 98.1% of participants had no ADHD-related training.…”
Section: Discussionsupporting
confidence: 53%
“…Only a handful of studies investigated the influence of other socio-demographic features on ADHD-specific attitudes. Results suggested that teaching students with ADHD diagnoses increased positive attitudes toward them ( Amha & Azale, 2022 ; Dessie et al, 2021 ), as did watching mass media as an information source about ADHD (Dessie et al). Furthermore, Cueli et al (2022) found that as teachers aged, their ADHD-specific attitudes became more negative, while having a close relationship with a student who had ADHD, having a relative with ADHD, or having ADHD themselves led to more positive opinions of their students with ADHD ( Flavian & Uziely, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%